Historical redlining and mortality in children, adolescents, and young adults with cancer in California, 2000-2019 - Karvonen, Kristine A; Vu, Annie; Lin, Katherine; Gibbons, Joseph; Mendoza, Jason A; Chow, Eric J; Winestone, Lena E; Gomez, Scarlett L (JNCI : Journal of the National Cancer Institute, 2025)
Historical redlining, or the Home Owners' Loan Corporation (HOLC) program's racially biased mortgage risk monitoring maps in the 1930s, is implicated in shaping modern neighborhoods and health outcomes. This retrospective cohort study evaluates the association between redlining and mortality in young cancer patients. Using the California Cancer Registry, we identified patients aged younger than 25 years diagnosed with malignant cancer between 2000 and 2019. HOLC maps were spatially joined with patient address at diagnosis to determine redlining status (A [best], B [still desirable], C [declining], D [hazardous]). Census tract-level US Census and American Community Survey data were appended to determine modern neighborhood characteristics. The Kaplan-Meier method was used to evaluate overall survival and multivariable Cox proportional hazards models to estimate the associations between HOLC grade and mortality, adjusting for clinical and multilevel social drivers of health. In total, 8108 patients resided in HOLC-graded neighborhoods among 51 084 patients statewide. Overall survival at 5 years was inferior for patients who resided in D-graded neighborhoods at diagnosis vs A-graded neighborhoods (80.3%, 95% confidence interval [CI] = 78.6% to 81.8%, vs 88.5%, 95% CI = 84.3% to 91.6%). Adjusting for clinical characteristics, patients in D-graded neighborhoods experienced greater mortality (hazard ratio [HR] = 1.32, 95% CI = 1.12 to 1.56) compared with those in A- and B-graded neighborhoods. Additional adjustment for insurance attenuated the effect (HR = 1.17, 95% CI = 1.00 to 1.36), and for neighborhood, socioeconomic status marginally attenuated the effect (HR = 0.96, 95% CI = 0.81 to 1.13). Findings suggest enduring legacy effects of historical redlining on young individuals with cancer potentially mediated social factors, including health insurance.